Occupancy of red‐naped sapsuckers in a coniferous forest: using LiDAR to understand effects of vegetation structure and disturbance. Issue 22 (2nd November 2015) - Holbrook, Joseph D.; Vierling, Kerri T.; Vierling, Lee A.; Hudak, Andrew T.; Adam, Patrick
Abstract: Red‐naped sapsuckers ( Sphyrapicus nuchalis ) are functionally important because they create sapwells and cavities that other species use for food and nesting. Red‐naped sapsucker ecology within aspen ( Populus tremuloides ) has been well studied, but relatively little is known about red‐naped sapsuckers in conifer forests. We used light detection and ranging (LiDAR) data to examine occupancy patterns of red‐naped sapsuckers in a conifer‐dominated system. We surveyed for sapsuckers at 162 sites in northern Idaho, USA, during 2009 and 2010. We used occupancy models and an information‐theoretic approach to model sapsucker occupancy as a function of four LiDAR‐based metrics that characterized vegetation structure and tree harvest, and one non‐LiDAR metric that characterized distance to major roads. We evaluated model support across a range of territory sizes using Akaike's information criterion. Top model support was highest at the 4‐ha extent, which suggested that 4 ha was the most relevant scale describing sapsucker occupancy. Sapsuckers were positively associated with variation of canopy height and harvested area, and negatively associated with shrub and large tree density. These results suggest that harvest regimes and structural diversity of vegetation at moderate extents (e.g., 4 ha) largely influence occurrence of red‐naped sapsuckers in conifer forests. Given the current and projected declines of aspen populations, it will be increasingly important to assess habitat relationships, as well as demographic characteristics, of aspen‐associated species such as red‐naped sapsuckers within conifer‐dominated systems to meet future management and conservation goals. Abstract : Habitat relationships of red‐naped sapsuckers have been well studied within aspen‐dominated stands, however, little is known in conifer‐dominated forests. We used LiDAR data to assess occupancy of red‐naped sapsuckers in a conifer‐dominated forest. Our results indicate that structural diversity at intermediate territory sizes is the most influential factor influencing occupancy, which has implications for forest manipulations such as logging.